Analisis Penggunaan Energi Surya Fotovoltaik Sebagai Sumber Energi Alternatif - Effendi, Ryan (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Solar photovoltaic energy is a renewable energy source that converts sunlight into electricity through the use of solar photovoltaic cells. The potential of solar energy is enormous, because the sun is an energy source that is abundantly available throughout the world. The method in this article is a qualitative method with literature study or Library Research. The purpose of this article is to analyze existing theories by looking at their comparison to previous theories in the research literature. The literature used is literature from research results or reviews that are recorded in national and international scientific articles that are relevant to the topic of this article. All articles used are sourced from the electronic literacy data search engine Mendeley and Google scholar. Based on the results of the literature review article on the results and discussion, it can be concluded that solar photovoltaic energy has high potential to be used as an alternative energy source in the long term in the future.